Descartes on intellectual joy and the intellectual love of god. - Agoff, Zachary (International Journal for Philosophy of Religion, 2024)
Descartes maintains that we can love God and that it is pleasant and morally beneficial to do so. In this essay, I examine the necessary conditions for such an intellectual love of God. I argue that the intellectual love of God is incited by a judgment that we are joined to God in reality, which is constitutive of an intellectual joy. I go on to show that the intellectual love of God is, itself, constituted by a stripping of our private interests in favor of God's divine will.